Implementasi Perma Nomor 1 Tahun 2016 Tentang Prosedur Mediasi dalam Perkara Perceraian di Pengadilan Agama Padang Kelas I A - Briantama, Albi; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
This study aims to identify and analyze the inhibiting factors in implementing Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in divorce cases at the Padang Religious Court Class I A. Although mediation is expected to reduce the burden on the courts and resolve disputes amicably, especially in complex divorce cases, its implementation at the Padang Religious Court still faces various obstacles. This research used a qualitative approach with a descriptive method, and data was collected through interviews and documentation studies. The results showed that although the PERMA No. 1 Year 2016 implementation has been going well, its effectiveness in the field is still low. This is reflected in the mediation success rate, which only reached 4.81%, with most divorce cases failing the mediation process. The main obstacles to implementation include the low legal awareness of the litigants, the lack of transparency of non-judge mediator fees, the limited ability of mediators, and the lack of socialization of mediation procedures by the Padang Class I A Religious Court.